1996
DOI: 10.1007/bf01690097
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genes coding for extended-spectrum SHV beta-lactamases in clinical isolates by a molecular genetic method, and comparison with the E test

Abstract: A highly sensitive and specific method, termed PCR/NheI, for the detection of genes coding for SHV extended-spectrum beta-lactamases (ESBL) in clinical isolates is presented. It is based on polymerase chain reaction (PCR) amplification of the blaSHV genes, followed by restriction with NheI. Due to the glycine (positive 238) (SHV-non-ESBL)-->serine (position 238) (SHV-ESBL) mutation, only PCR fragments from the genes coding for SHV-ESBLs were cleaved. A commercially available test for ESBLs, the E test ESBL, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(148 citation statements)
references
References 23 publications
6
142
0
Order By: Relevance
“…Similarly, low transconjugation success was also reported by other workers in Switzerland and Germany [19,34]. Franiczek et al [35] also reported that none of the four E. coli isolates could transfer their resistance gene to other recipient strains.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, low transconjugation success was also reported by other workers in Switzerland and Germany [19,34]. Franiczek et al [35] also reported that none of the four E. coli isolates could transfer their resistance gene to other recipient strains.…”
Section: Discussionmentioning
confidence: 55%
“…Some ESBLs may fail to reach a level to be detected by disk diffusion tests but result in treatment failure in the infected patient. Nuesch-Inderbinen and Hachler (1996) reported that molecular methods appear sensitive, are expensive, time consuming and require specialized equipment and expertise. However, definitive identification is possible only by molecular detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…Digestion of bla SHV with NheI was carried out in order to identify Gly238→Ser mutation associated with the hydrolysis of third generation cephalosporins [19]. Sequencing of bla CTX-M and bla TEM genes were performed for single representatives of major clones [17,20].…”
Section: Detection Of β-Lactamase Genesmentioning
confidence: 99%